2022
DOI: 10.3389/fcvm.2022.761917
|View full text |Cite
|
Sign up to set email alerts
|

Patient Prosthesis Mismatch After SAVR and TAVR

Abstract: Patient-prosthesis mismatch (PPM) remains one out of many factors to be considered during decision-making for the treatment of aortic valve pathologies. The idea of adequate sizing of a prosthetic heart valve was established by Rahimtoola already in 1978. In this article, the author described the phenomenon that the orifice area of a prosthetic heart valve may be too small for the individual patient. PPM is assessed by measurement or projection of the prosthetic effective orifice area indexed to body surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Looking at post-procedural mean transvalvular gradient, THVs performed better than surgical aortic valve prostheses. This superiority of THVs is well-known, in particular with the use of supra-annular devices (60.8% in our series) ( 31 33 ). This is a point in favor of TAVR when discussing the best therapeutic option in the case of LFLG AS, as the more complete is the relief of afterload mismatch, the higher is the probability of LV recovery ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 73%
“…Looking at post-procedural mean transvalvular gradient, THVs performed better than surgical aortic valve prostheses. This superiority of THVs is well-known, in particular with the use of supra-annular devices (60.8% in our series) ( 31 33 ). This is a point in favor of TAVR when discussing the best therapeutic option in the case of LFLG AS, as the more complete is the relief of afterload mismatch, the higher is the probability of LV recovery ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 73%
“…It seems that PPM is associated with an impaired outcome in patients with reduced ejection fraction [ 52 ]. This has led some experts to prioritizing self-expanding THV in this patient group [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the present study showed lower frequency of PPM in SEVs than in Lotus and Sapien 3. However, the results should be interpreted with caution because the severity of PPM, which was assessed by transthoracic echocardiogram derived indexed effective orifice area (EOA), was more often overestimated in Sapien 3 compared with SEVs due to the pressure recovery phenomenon 101 , 102 . Fukui et al demonstrated that using computed tomography-derived EOA instead of transthoracic echocardiogram derived EOA changed the frequency of PPM observed with SEVs and Sapien 3 from 11.1% versus 24.6% ( P = 0.002) to 2.3% versus 4.2% ( P = 0.399) 35 .…”
Section: Discussionmentioning
confidence: 99%